PERAN TOKOH MASYARAKAT TERHADAP PENGEMBANGAN PARIWISATA HALAL DI PANTAI THE LEGEND PADELEGAN PAMEKASAN - Uswatun Hasanah; Rudi Hermawan (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2021)
This study discusses the Role of Community Leaders in Halal-Based Tourism Development at The Legend Padelegan Beach, Pamekasan, where this tourist attraction has an attraction to be preserved and has enormous potential to be developed, as a tourist destination, especially for people around The Legend beach. Padelegan, Pademawu District, Pamekasan Regency. This study uses qualitative research, where the data collected is not in the form of numbers but the data comes from the field directly collected using interview scripts. The results of this study indicate that the role or participation of the community in the development of coastal tourism The legend is so enthusiastic in the tourism development sector, such as maintaining the cleanliness of the beach area so as not to disturb the comfort of tourists, maintaining the safety of tourist transportation, making things to attract visitors and many others.Keywords: role of community leaders, impact, halal tourism